Effect of thawing temperature on the motility recovery of cryopreserved human spermatozoa - Calamera, Juan C. (2010)
Objective To investigate the effects of thawing temperature on sperm function after cryopreservation. The technical aspects of sperm cryopreservation have significantly improved over the last few decades. However, a standard protocol designed to optimize sperm motility recovery after thawing has not yet been established. Design Prospective study. Setting Private infertility institute and university-based research laboratory. Patient(s) Eighty consenting normozoospermic patients consulting for infertility. Intervention(s) Spermatozoa from donor semen samples were thawed at different temperatures. Main Outcome Measure(s) Sperm motility, viability, adenosine-5'-triphosphate (ATP) content, acrosomal status, and DNA integrity were evaluated as a function of thawing temperature in cryopreserved human sperm samples. Result(s) Thawing at 40°C resulted in a statistically significant increase in sperm motility recovery compared with thawing at temperatures between 20°C and 37°C. There were no statistically significant differences in sperm viability, acrosomal status, ATP content, and DNA integrity after thawing at 40°C compared with thawing at temperatures between 20°C and 37°C. Conclusion(s) Sperm thawing at 40°C could be safely used to improve motility recovery after sperm cryopreservation.